Oxidative modification of proteins in the synovial fluid of patients with osteoarthritis after SARS-CoV 2-infection - Бородін Сергій; Дворщенко, Катерина Олександрівна (Київський національний університет імені Тараса Шевченка, 2023)
The pandemic of coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has made a serious public health threat worldwide. It has caused many complications and deaths, so millions of people are at risk in more and more countries. A special group consists of patients with chronic diseases, particularly osteoarthritis. It is known that the development of osteoarthritis is associated with oxidative stress and excessive production of free radicals. Proteins are highly sensitive to free radical oxidation, so their oxidation level reflects the oxidant-antioxidant balance in the body. The aim of the work was to determine the concentration of products of oxidative modification of proteins and sulfhydryl groups in the synovial fluid of patients with osteoarthritis after SARS-CoV2 infection. All study participants were divided into two groups. The first group (n=22) is patients with osteoarthritis of the knee joints II-III degree. The second group (n=14) is patients with osteoarthritis of the knee joints II-III degree, who suffered a mild and moderate form of COVID-19 6-9 months ago. In the conducted studies, the products of protein oxidation in the synovial fluid of patients of all experimental groups were evaluated. The concentration of products of oxidative modification of proteins was determined by the level of carbonyl derivatives, which are detected in the reaction with 2,4-dinitrophenylhydrazine. The concentration of total, protein-bound and non-protein sulfhydryl (SH) groups was measured by the Ellman method. Processing of research results was carried out using generally accepted methods of variational statistics. It was established that in the synovial fluid of patients with osteoarthritis of the knee joints who contracted COVID-19, the concentration of products of oxidative modification of proteins increased. Under the same experimental conditions, the concentration of sulfhydryl groups decreased. The detected changes indicate a violation of the oxidant-antioxidant balance in the synovial fluid of patients with osteoarthritis after SARS-CoV-2 infection. This indicates the prevalence of free radical processes and the development of oxidative stress directly in the joint. Our results indicate that patients with osteoarthritis may develop more severe joint damage after infection with COVID-19.

Пандемія коронавірусної хвороби 2019 року (Coronavirus disease 2019, COVID-19), спричинена важким гострим респіраторним синдромом коронавірусу 2 (Severe acute respiratory syndrome-related coronavirus 2, SARS-CoV-2), створила серйозну загрозу громадському здоров'ю в усьому світі. Вона спричинила розвиток багатьох ускладнень і смертей, тому мільйони людей перебувають під загрозою у все більшій кількості країн. Особливу групу становлять хворі на хронічні захворювання, зокрема остеоартрити. Відомо, що розвиток остеоартритів пов'язаний з окисним стресом і надлишковим продукуванням вільних радикалів. Білки високочутливі до вільнорадикального окиснення, тому рівень їхнього окиснення відображає окисно-антиоксидантний баланс в організмі. Метою роботи було визначити вміст продуктів окисної модифікації білків і сульфгідрильних груп у синовіальній рідині хворих на остеоартрит після SARS-CoV2-інфекції. Усі учасники дослідження були поділені на дві групи: перша (n=22) – пацієнти з остеоартритом колінних суглобів II–III ступеня, друга (n=14) – пацієнти з остеоартритом колінних суглобів II–III ступеня, які перенесли легку й середньотяжку форму COVID-19 6 – 9 місяців тому. Було досліджено продукти окиснення білків у синовіальній рідині пацієнтів усіх дослідних груп. Вміст продуктів окисної модифікації білків визначали за рівнем карбонільних похідних, які виявляються в реакції з 2,4 динітрофенілгідразином. Вміст загальних, білок-зв'язаних і небілкових сульфгідрильних (SH-) груп вимірювали за методом Елмана. Обробку результатів проводили загальноприйнятими методами варіаційної статистики. Установлено, що у синовіальній рідині пацієнтів з остеоартритом колінних суглобів, які перехворіли на COVID-19, вміст продуктів окисної модифікації білків зростав. За тих самих експериментальних умов вміст сульфгідрильних груп знижувався. Виявлені зміни свідчать про порушення окисно-антиоксидантної рівноваги у синовіальній рідині хворих на остеоартрит після SARS-CoV-2-інфекції. Це вказує на превалювання вільнорадикальних процесів і розвиток окисного стресу безпосередньо в суглобі. Отримані результати свідчать, що у хворих на остеоартрит після інфікування COVID-19 можливий розвиток більш важкого ураження суглобів.
Окисна модифікація білків у синовіальній рідині хворих на остеоартрит після SARS-CoV2-інфекції
Keywords: SARS-CoV-2; остеоартрит; синовіальна рідина; окисна модифікація білків; osteoarthritis; synovial fluid; oxidative modification of proteins